Local content in procurement : creating local jobs and competitive domestic industries in supply chains - Warner, Michael, 1963- (Greenleaf Publishing, 2011)
Local content in procurement is the first book of its kind. Recognising the substantial economic and social value brought to host countries and local communities through the procurement practices of large private and public companies, this book by Dr Michael Warner - Director of the consultancy firm Local Content Solutions and former architect of the Local Content standards for BG Group - provides a first-hand account of the Local Content regulations, strategies and procurement processes needed to realise these social benefits. Acknowledging that the employment and industrial benefits of large-scale procurement have been sorely overlooked, this book is both a how-to manual and a thoughtful insight into the challenge of creating sustainable jobs and competitive national industries through expenditure on bought-in goods and services. Local Content in Procurement has been written for those working for the procurement, strategy and social responsibility departments of major private and public companies and international suppliers, for industrial and economic policy-makers and regulators of local content, and for all those involved in the management of procurement expenditure to develop national and local industries.